THE EFFECT OF POLITICAL CONNECTIONS, INDEPENDENT COMMISSIONERS, AND INSTITUTIONAL OWNERSHIP ON TAX AVOIDANCE IN LQ45 COMPANIES 2015-2020 PERIOD - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2026)
The purpose of this study was to analyze the effect of political connections, independent commissioners, institutional ownership on tax avoidance. The data used is secondary data. The population in this study were LQ45 companies on the Indonesia Stock Exchange in 2015-2020 with a total sample of 45 companies that met the criteria by using purposive sampling technique. The independent variables used are political connections, independent commissioners, and institutional ownership which are tested for their influence on the dependent variable, namely tax avoidance. The analytical technique used is multiple linear regression analysis using t test for hypothesis testing. The results of the study show that political connections have no significant effect on tax avoidance. Independent Commissioner has a negative and significant effect on tax avoidance. Institutional ownership has a positive effect on tax avoidance. Overall, the dependent variable above simultaneously affects tax avoidance.